Pengaruh Pestisida Nabati Limbah Batang Tembakau Virginia Terhadap Keragaman Kumbang Koksi Sebagai Predator Hama Pada Tanaman Kentang (Solanum Tuberosum L.) - Maulana Aziz, Lutfi; Sarjan, Muhammad; Haryanto, Hery (Journal of Microbiology, Biotechnology and Conservation, 2025)
This study aims to determine the effect of vegetable pesticides from virginia tobacco stem waste on the diversity of the koksi beetle predators on potato plants. The method used is an experimental method with direct experiments in the field. The experimental design used was a randomized block design (RAK) with 6 treatments, namely P0 (control), P1 (abamectin), P2 (vegetable insecticide of Virginia tobacco stem waste 2 ml/l), P3 (vegetable insecticide of Virginia tobacco stem waste 4 ml/l). l), P4 (vegetable insecticide of Virginia tobacco stem waste 6 ml/l), and P5 (vegetable insecticide of Virginia tobacco stem waste 8 ml/l). This research was conducted in Sembalun Bumbung Village, Sembalun District, East Lombok Regency, West Nusa Tenggara from August 2020 to November 2020. The results showed that treatment at the concentration of P5 (vegetable pesticide from virginia tobacco stem waste 8 ml/l) showed a suppression value. The diversity and abundance index of the predators of the koksi beetle were the most influential compared to the treatment of several concentrations of other vegetable pesticides, while the application of botanical pesticides with various concentrations was not able to suppress the predatory population of the koksi beetle in the species Cheliomenes sexmaculata and Coccinella transveralis and was able to suppress the population of Coleophora inaqualis. Cheilomenes sexmaculata species has the highest population compared to the other 2 species.